Effect of experience of severe stroke on subjective valuations of quality of life after stroke. Issue 5 (1st May 2001) - Murphy, R; Sackley, C M; Miller, P; Harwood, R H
Abstract : Previous work suggests that the quality of life associated with severe disability after stroke is rated very poorly by members of the public, often as being worse than death. Other evidence suggests that experience of illness alters perceptions of its severity. This was tested for severe stroke. Eleven patients with severely disabling stroke, but able to complete a standard gamble interview, 22 age and sex matched controls, and 20 health professionals participated. A standard gamble interview was carried out to determine the quality of life (utility) associated with three hypothetical scenarios representing mild, moderate, and severe stroke, and current health. A sample was retested for reliability, and comparisons were made with other measures of health status. All three subject groups showed wide variation in the utilities they attached to each of the scenarios. The control subjects' valuations were lower than those of either patients or staff members, especially for moderate stroke (median 0.30, 0.73, and 0.68 respectively). There were weak to moderate correlations between utilities and other measures of health status including the Barthel index ( r =0.51) and Rivermead mobility score ( r =0.24). Test retest-reliability was modest (reliability coefficient 0.75), but indicators of the internal validity of the results were good. In conclusion, it cannot be assumed that general population valuations are valid for patient groups. In clinical practice it is unsafe to make any assumption about subjective quality of life after stroke, due to the wide range of valuations given, although many people rate severe and moderate stroke at least as bad as death.